(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Metformin is an oral antidiabetic agent used as in the treatment of T2DM. A fearsome complication of the use of metformin is lactic acidosis. A nineteen-year-old woman was unconscious and cyanotic in her home. It has been found that about 50 grams of metformin is taken for the purpose of suicide. Glaskow Coma Scale 4/15, Blood Pressure: 70 / 30mmHg, lactic acidosis was detected. Despite the hemodialysis procedure, the patient passed away. Metformin, the keystone of diabetes treatment, inhibits gluconeogenesis, improve insulin resistance, and is excreted in the kidneys without being metabolized. Metformin rarely makes lactic acidosis. High doses of metformin and renal impairment facilitate the formation of lactic acidosis. There is a direct relationship between the degree of lactic acidosis and mortality. Lactic acidosis is thought to be due to the accumulation of lactate by the inhibition of gluconeogenesis. Metformin intoxication may kill the patient through lactic acidosis.